2006
DOI: 10.1124/mol.106.025130
|View full text |Cite
|
Sign up to set email alerts
|

Varenicline Is a Partial Agonist at α4β2 and a Full Agonist at α7 Neuronal Nicotinic Receptors

Abstract: Varenicline, a new nicotinic ligand based on the structure of cytisine, has recently been approved by the U.S. Food and Drug Administration for use as a smoking cessation aid. Varenicline has been shown to be a partial agonist of ␣4␤2 receptors, and in equilibrium binding assays, it is highly selective for the ␣4␤2 receptor. In this study, we have examined the functional activity of varenicline at a variety of rat neuronal nicotinic receptors expressed in Xenopus laevis oocytes and assayed under two-electrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
465
2
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 524 publications
(499 citation statements)
references
References 20 publications
24
465
2
5
Order By: Relevance
“…Also, the superagonism displayed by (Ϯ)-epibatidine at the receptor differs from the full agonism reported for this agonist at WT ␣6␤4 (23). As for the other agonists, the partial agonist activity of (Ϫ)-cytisine at C6 F223L ␤4␤3 is in concordance with previous studies of the agonist at chick ␣6-human ␤4 and ␣3␤4 nAChRs (21, 34 -36) just as the 32% efficacy exhibited by varenicline seems plausible considering its partial agonist activity at ␣4␤2, ␣3␤4, and ␣6 NTD /␣3 TMD/ICL ␤2␤3 nAChRs (37,38). Finally, the biphasic concentration-response relationship exhibited by sazetidine A seems plausible in light of previous reports of sazetidine A being a potent agonist and desensitizing agent of ␣4␤2 nAChRs (39,40).…”
Section: Journal Of Biological Chemistry 33711supporting
confidence: 75%
“…Also, the superagonism displayed by (Ϯ)-epibatidine at the receptor differs from the full agonism reported for this agonist at WT ␣6␤4 (23). As for the other agonists, the partial agonist activity of (Ϫ)-cytisine at C6 F223L ␤4␤3 is in concordance with previous studies of the agonist at chick ␣6-human ␤4 and ␣3␤4 nAChRs (21, 34 -36) just as the 32% efficacy exhibited by varenicline seems plausible considering its partial agonist activity at ␣4␤2, ␣3␤4, and ␣6 NTD /␣3 TMD/ICL ␤2␤3 nAChRs (37,38). Finally, the biphasic concentration-response relationship exhibited by sazetidine A seems plausible in light of previous reports of sazetidine A being a potent agonist and desensitizing agent of ␣4␤2 nAChRs (39,40).…”
Section: Journal Of Biological Chemistry 33711supporting
confidence: 75%
“…number of withdrawal symptoms, withdrawal severity) and the efficacy of pharmacotherapeutic treatments for smoking cessation. In support, it has been shown that variations in CHRNA4 are associated with smoking cessation outcomes [75], and it is possible that polymorphisms in nAChR subunit genes may modulate the effects of nicotine replacement therapy and varenicline (a α4β2* partial agonist and α7 nAChR full agonist) [21,118] on smoking cessation. Furthermore, given that the protein products of these genes are known to interact with each other to form receptors, it is possible that interactions between nAChR subunit genes may have a greater influence on smoking phenotypes than an individual nAChR subunit gene; thus, additional research should investigate possible gene-gene interactions between nAChR subunit genes.…”
Section: The Chrnb3-chrna6 and Chrna5-chrna3-chrnb4 Gene Clustersmentioning
confidence: 99%
“…In fact, medications that effectively increase acetylcholine by inhibiting acetylcholinesterase reduce the positive subjective effects of meth (De La Garza et al, 2008a; De La Garza 2008b; De La Garza et al, 2012). Additionally, varenicline (Chantix ® ), a partial α4β2 and full α7 nicotinic acetylcholine receptor agonist, (Coe et al, 2005a; Mihalak et al, 2006) can reduce the positive subjective effects of meth in humans, an effect that may reflect nAChR agonism reversing dopaminergic hypofunction (Verrico et al, 2014; Zorick et al, 2009). …”
Section: Introductionmentioning
confidence: 99%